Regional differences in the green use level of cultivated land in the Heilongjiang reclamation area - Du, Guoming; Xie, Jing; Hou, Dawei; Yu, Fengrong (Frontiers in Environmental Science, 2023)
It is essential to scientifically evaluate the Green Use Level of Cultivated Land (GUL-CL) and measure the regional differentiation of GUL-CL to promote the sustainable use of cultivated land. Based on the statistical data of the Heilongjiang Reclamation Area (HRA) in 2020, this study analyzed the regional differences in GUL-CL in the HRA using the entropy power method and a coupled coordination degree model. The results show that the degree of GUL-CL in the study area is generally well-developed, but internal differences exist. Specifically, the GUL-CL ranges from 0.590 to 38.179, with a mean value of 8.818. Additionally, 29.204% of the total farms are above the higher level, mainly in Jiansanjiang and Baoquanling. In environmental protection practices, the high-level areas are concentrated primarily on the Songnen Plain Reclamation Area. Or, the Sanjiang Plain Reclamation Area positively presents significant effects on resource conservation. In the study area, spatial intensification and output efficiency are relatively balanced. The coupling coordination degree of green use of cultivated land(GU-CL) (0.20-0.50) is at a low coupling coordination stage. Consequently, this study can provide practical knowledge for the GU-CL in the black soil region of Northeast China.